Elderly location monitoring system with LoRa (iLocation) - Hamzah, Nurhaziqah Izzati; Zainal Rashid, Siti Hajar; Talib, Muhamad Lazim; Ahamad, Noor Annys Fareyhah; Nazir, Nur Safiya; Che Muda @ Hamdzah, Muhammad Mahathir; Abdul Hamid, Ahmad Fakhrul Nazmi (Academica Press Solutions, 2024)
The Wireless Long Range (LoRa) technology is a wireless communication system that provides extended range and energy efficiency. Renowned for its exceptional energy efficiency and extensive coverage, this technology surpasses the limitations of GPS and BLE. The objective of this research is to enhance the surveillance of the whereabouts of elderly caregivers by employing LoRa devices. The primary aims of this research are to showcase the use of the iLocation system for elder caretakers and to offer real-time displays of position coordinates. The present study utilizes a research methodology based on the Internet of Things (IoT) framework, with a particular focus on the application of LoRa technology for the purpose of tracking locations in real-time. IoT leverages connectivity to provide communication, instantaneous data analysis, and intelligent decision-making among diverse objects. This system showcases the advantages of LoRa technology, encompassing its energy efficiency and wide-ranging coverage, while also illustrating its potential application in monitoring the elderly population. This technology enables caregivers to monitor the real-time whereabouts of elderly individuals. In addition, elderly individuals have the choice to send a warning message to their carer in case of any unexpected situation. The use of LoRa technology in the Elderly Location Monitoring System offers a unique and practical solution to meet the needs of caregivers.